Liposomal irinotecan with fluorouracil and leucovorin as salvage treatment for advanced biliary tract cancer refractory to gemcitabine and cisplatin - Kim, Hyunho; Shin, Kabsoo; Park, Hyung Soon; Hong, Tae Ho; Kim, Younghoon; Lee, Sung Hak; Kim, In-Ho; Lee, MyungAh; Park, Se Jun (Frontiers in Oncology, 2025)
IntroductionThe combination of liposomal irinotecan with fluorouracil and leucovorin (Nal-IRI/FL) has shown efficacy in phase II trials for advanced biliary tract cancer (BTC) following gemcitabine-cisplatin (GP) therapy. However, its effectiveness and safety in real-world clinical settings have not been well established. This study aimed to assess the real-world outcomes of Nal-IRI/FL in BTC patients who experienced disease progression after gemcitabine-based treatment.Materials and methodsThis retrospective, multicenter study evaluated patients with advanced BTC who received Nal-IRI/FL following progression on GP-based therapy between January 2022 and December 2024. Survival outcomes, radiologic responses, toxicities, and molecular alterations were evaluated, with key findings compared against those reported in prior clinical trials.ResultsA total of 93 patients were included. The median progression-free survival (PFS) and overall survival (OS) were 2.1 and 4.2 months, respectively. Among 76 radiologic response evaluable patients, median PFS and OS were 2.5 and 5.0 months. The disease control rate was 40.8%, and objective response rate was 7.5%. Higher disease burden and poor performance status were associated with inferior outcomes. Efficacy did not significantly differ between second- and third-line settings or based on RAS or TP53 mutation status. Hematological toxicities were common, including grade ≥3 neutropenia (38.7%) and febrile neutropenia (7.5%). The median relative dose intensity was 0.69. Treatment-related death occurred in 4 patients (4.3%).ConclusionsNal-IRI/FL showed modest effectiveness in real-world settings, with outcomes generally less favorable than clinical trials, potentially reflecting patient characteristics. Its efficacy was consistent across treatment lines and mutation subgroups, including patients with RAS or TP53 mutations. Careful patient selection and proactive supportive care are essential. Further studies are warranted to clarify its role across diverse populations.